The derivative as a probabilistic synthesis of past and future data and remaining useful life prediction - Damasceno, Berenice Camargo [UNESP]; Barbanti, Luciano [UNESP]; Kuzminskas, Hadamez [UNESP]; Bazani, Márcio Antonio [UNESP] (Springer Nature, 2017)
The concept of remaining useful life (RUL) is crucial when dealing with mechanical systems. RUL is taken into account in a system through a series of prognostics and the study of stability in a related data series. This paper is focused on a powerful optimal technique in prognosis coming from the Grünwald-Letnikov definition of derivative.
Keywords: Forecasting; Grünwald-Letnikov derivative; Probability